Brand name as a heuristic cue: The effects of task importance and expectancy confirmation on consumer judgments - Maheswaran, Durairaj; Mackie, Diane M.; Chaiken, Shelly (Journal of Consumer Psychology, 1992)
Previous research on brand name utilization in consumer judgments has yielded mixed results. In this study, we attempted to understand brand name effects within the framework of the heuristic‐systematic model. Subjects read a message that portrayed a new product as possessing either important or unimportant attributes, and the product was associated with either a favorable brand name or an unfavorable brand name. Brand name valence was thus either congruent or incongruent with attribute importance. Accuracy motivation was also manipulated by varying the importance of subjects' processing task. Results show that low‐task importance subjects' evaluations were influenced only by brand name valence. High‐task importance subjects' evaluations were affected only by attribute importance in the incongruent conditions, whereas both attribute importance and brand name valence influenced evaluations in the congruent conditions. The findings indicate that both consumers' level of motivation, and the extent to which brand name based expectations are confirmed by subsequent processing of attribute information moderate brand name utilization. Also, the results extend previous research relevant to the heuristic‐systematic model's additivity and attenuation assumptions.